A Comprehensive Analysis of the Genetic Diversity of Plasmodium falciparum Histidine-Rich Protein 2 (PfHRP2) in the Brazilian Amazon - Costa, Gabriel Luíz; Mascarenhas, Maria Eduarda Pereira; Martin, Thamires Oliveira Gasquez; Fortini, Laura Guimarães; Louzada, Jaime; Pereira, Dhélio Batista; Aguiar, Anna Caroline Campos; Carvalho, Luzia Helena; de Brito, Cristiana Ferreira Alves; Fontes, Cor Jesus Fernandes; de Sousa, Tais Nóbrega (Frontiers in Cellular and Infection Microbiology, 2021)
Early diagnosis and treatment are fundamental to the control and elimination of malaria. In many endemic areas, routine diagnosis is primarily performed microscopically, although rapid diagnostic tests (RDTs) provide a useful point-of-care tool. Most of the commercially available RDTs detect histidine-rich protein 2 (HRP2) of Plasmodium falciparum in the blood of infected individuals. Nonetheless, parasite isolates lacking the pfhrp2 gene are relatively frequent in some endemic regions, thereby hampering the diagnosis of malaria using HRP2-based RDTs. To track the efficacy of RDTs in areas of the Brazilian Amazon, we assessed pfhrp2 deletions in 132 P. falciparum samples collected from four malaria-endemic states in Brazil. Our findings show low to moderate levels of pfhrp2 deletion in different regions of the Brazilian Amazon. Overall, during the period covered by this study (2002-2020), we found that 10% of the P. falciparum isolates were characterized by a pfhrp2 deletion. Notably, however, the presence of pfhrp2-negative isolates has not been translated into a reduction in RDT inefficacy, which in part may be explained by the presence of polyclonal infections. A further important finding was the discrepancy in the proportion of pfhrp2 deletions detected using two assessed protocols (conventional PCR versus nested PCR), which reinforces the need to perform a carefully planned laboratory workflow to assess gene deletion. This is the first study to perform a comprehensive analysis of PfHRP2 sequence diversity in Brazilian isolates of P. falciparum. We identified 10 PfHRP2 sequence patterns, which were found to be exclusive of each of the assessed regions. Despite the small number of PfHRP2 sequences available from South America, we found that the PfHRP2 sequences identified in Brazil and neighboring French Guiana show similar sequence patterns. Our findings highlight the importance of continuously monitoring the occurrence and spread of parasites with pfrhp2 deletions, while also taking into account the limitations of PCR-based testing methods associated with accuracy and the complexity of infections.